CYBERLAUNDERING AND THE FUTURE OF CORRUPTION IN AFRICA - Mabunda, Sagwadi (Journal of Anti-Corruption Law, 2023)
Corruption has been given considerable attention as one of the major causes of the socio-economic ills that plague Africa. Statistics reveal that staggering amounts of money are lost annually to corruption. Many discussions about corruption focus on its meaning, its causes and its impact but one pertinent issue goes unexamined: what happens to the money? The answer is money laundering. And while we are trying to grapple with the challenges of today, it is imperative that we consider the troubles that await. This paper discusses the relationship between corruption and money laundering, with a focus on the technique of cyberlaundering. It recommends that regional research units be created to address the issues raised.